Dismantling Ideology and Power of Corporate Financial Statements - Binti Shofiatul Jannah; Imam Buchori (Yayasan Rumah Peneleh, 2020)
This article aims to explain that critical content analysis can be employed to dismantle ideology and power behind rhetoric and visual portraits conveyed in financial statement. Literature study was used as methodology. The results indicate that reality can be deconstructed by means of lslamic teaching.